2017
DOI: 10.1016/j.antiviral.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

4′-Azidocytidine (R1479) inhibits henipaviruses and other paramyxoviruses with high potency

Abstract: The henipaviruses Nipah virus and Hendra virus are highly pathogenic zoonotic paramyxoviruses which have caused fatal outbreaks of encephalitis and respiratory disease in humans. Despite the availability of a licensed equine Hendra virus vaccine and a neutralizing monoclonal antibody shown to be efficacious against henipavirus infections in non-human primates, there remains no approved therapeutics or vaccines for human use. To explore the possibility of developing small-molecule nucleoside inhibitors against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Recombinant reporter virus assays were performed as previously described [27,35]. In brief, 10 4 cells pretreated with serial dilutions of GRFT for 1 hour were infected with the above-mentioned reporter viruses (without washing) for 24-72 hours and then assayed either for GFP, GFP + cells, or for Renilla luciferase activity.…”
Section: Reporter Virus and Minigenome Assaysmentioning
confidence: 99%
“…Recombinant reporter virus assays were performed as previously described [27,35]. In brief, 10 4 cells pretreated with serial dilutions of GRFT for 1 hour were infected with the above-mentioned reporter viruses (without washing) for 24-72 hours and then assayed either for GFP, GFP + cells, or for Renilla luciferase activity.…”
Section: Reporter Virus and Minigenome Assaysmentioning
confidence: 99%
“…ddBCNAs (see sections "Poxviridae "and "Flaviviridae"; [99]) and the plant extract naphthoquinone droserone have anti-measles activities in vitro [87]. The nucleoside-analogue 4′-azidocytidine (R1479; balapiravir) was developed to inhibit HCV [108], paramyxoviruses, and filoviruses in vitro [63], but showed low efficacy and high toxicity in hepatitis C patients in early clinical trials [108].…”
Section: Paramyxoviridaementioning
confidence: 99%
“…In a recent in-vitro study, favipiravir has been demonstrated its activity against viral replication and transcription in NiV and HeV (Dawes et al, 2018). R1479 (4 0 -azidocytidine) has also been reported to inhibit different members from Paramyxoviridae family (Hotard, He, Nichol, Spiropoulou, & Lo, 2017). However, despite these efforts for developing such inhibitors, no approved drugs are available yet for efficient use in humans.…”
Section: Introductionmentioning
confidence: 99%